Uji Daya Hasil Hibrida Cabai Besar (Capsicum annuum L.) di Dataran Rendah Karawang - Djayadiningrat, Muhamad Hyar; Syafi’i, Muhammad; Syukur, Muhamad (JURNAL AGROPLASMA, 2023)
Red chili (Capisum annuum L.) is a horticultural commodity that has high economic value. Chili production in Indonesia is increasing, but it’s still unable to meet the needs of the Indonesian people, so it is necessary to assemble high-quality and high-yielding hybrid seeds. This study aims to identify the quantitative characters of 4 IPB hybrid chili lines with 6 commercial varieties as a comparison. This research was conducted in April-September 2022 at the Experimental Land PERURI in Teluk Jambe Timur District, Karawang Regency. The method used was an experimental method with a single factor randomized block design (RAK) with chili genotypes as the treatment. The treatment consisted of 4 expected lines namely F1.074005, F1.074003, F1.374005 and F1.374003 and 6 commercial control varieties namely CH3, Baja, Balebat, Elegance, Imperial 10 and Gada. Each genotype was repeated 3 times so that there were 30 experimental units and each experimental unit consisted of 10 plants. The data obtained will be analyzed at the 5% level F test with the Duncan Multiple Range Test (DMRT). Based on the experimental results, it was shown that there were treatments that had a significant effect on the yield component of fruit weight per plant, namely genotypes F1.374003 and F1.074003. The hopeful hybrid F1.374003 also gave the highest yield in the productivity yield component (4.67 tonnes/ha).